Chain response of microbial loop to the decay of a diatom bloom in the East China Sea. (February 2016) - Wu, Linnan; Lin, Shiquan; Huang, Lingfeng; Lu, Jiachang; Chen, Wenzhao; Guo, Weidong; Zhang, Wuchang; Xiao, Tian; Sun, Jun
Abstract: Algal bloom has been regarded as one of the key causes for the summer hypoxia phenomena in the bottom water adjacent to the Yangtze River estuary in the East China Sea. Although a series of biological processes within microbial loop are involved in the development of oxygen depletion during the bloom decay, little has been known about the dynamics of microorganisms in response to the decaying process of the bloom through trophic interaction context. Here, we report some preliminary results of our observations about the response of microbial loop to the bloom decay, based on the onboard incubation experiments for 10 days during a diatom bloom near the Yangtze River estuary in August, 2011. Light and dark incubations were conducted to simulate the bloom decay inside and below the euphotic layer, respectively. In the first stage of bloom decay (Day 0 to Day 4), rapid response was found in heterotrophic bacteria (HB) and ciliate growth, which was in accordance with the decrease of total Chl a, indicating a "bottom-up" control at the early stage of bloom decay. However, the increase of heterotrophic nanoflagellates (HNF) abundance was rather inconspicuous, suggesting predation pressure on HNF from ciliate or other predator at this stage. In the second stage (Day 4 to Day 8), HB and ciliate decreased rapidly with the increase of HNF, revealing the release of HNF form ciliate predation, which suggested a "top-down" control. In the last stage of our experiment (Day 8 to Day 10), the trophic interactions were more complex, but it also implied a "top-down" control within the microbial loop. Meanwhile, virus had been monitored in the whole process of our incubations. It was found that virus lysed microalgae at the first stage, and lysed HB at the second stage. In addition, the bacterial mortality was principally caused by HNF grazing in the light-sufficient incubations and by viral lysis in the light-insufficient incubations. Our results suggest tight trophic interactions within the microbial loop in the decaying process of the algal bloom, which may assist our understanding of the role of microbial loop in hypoxia formation in coastal waters.